2012
DOI: 10.1007/s00436-012-2991-x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Toxoplasma gondii in infected murine tissues

Abstract: Laboratory maintenance of the RH strain of Toxoplasma gondii is generally done by passage in mice, in vitro propagation in fibroblasts, or cryopreservation of peritoneal exudates from mice infected with T. gondii. To explore alternative techniques for preserving laboratory T. gondii tachyzoites, we propose a new method of freezing tissues from infected mice. The effect of storage of T. gondii tissue tachyzoites in two different cryoprotectant combinations and at two different temperatures was studied. The live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In spite of the low parasite burden in the liver described only until the 42 nd day after infection by Djurkovic-Djakovic et al, (2012) in experimental murine chronic infections caused by the Me-49 strain, our study shows that the hepatic injury persists until 120 days after the infection. Zheng et al (2012) demonstrated that it is possible to cause experimental toxoplasmosis in mice infected with cryopreserved liver tissues, which indicates the presence of the parasite in this organ during long chronic infections such as 120 days.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In spite of the low parasite burden in the liver described only until the 42 nd day after infection by Djurkovic-Djakovic et al, (2012) in experimental murine chronic infections caused by the Me-49 strain, our study shows that the hepatic injury persists until 120 days after the infection. Zheng et al (2012) demonstrated that it is possible to cause experimental toxoplasmosis in mice infected with cryopreserved liver tissues, which indicates the presence of the parasite in this organ during long chronic infections such as 120 days.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of T. gondii tachyzoites in the liver has been demonstrated by several authors in experimental models (Milovanovic et al, 2009;Djurkovic-Djakovic et al, 2012;Zheng et al, 2012) however there is not a description of the injuries caused by this parasite on this vital organ.…”
Section: Introductionmentioning
confidence: 99%
“…8 Maintenance of Toxoplasma strain by cryopreservation is another method that needs the availability of tanks of liquid nitrogen but carries many hazards for laboratory workers. 9 To avoid the above mentioned drawbacks in maintaining active tachyzoites, the present study was conducted to characterize the appropriate conditions for prolonged in-vitro maintenance of T.g. T. harvested from peritoneal fluids of inoculated mice in cell free-fluid media under different temperature in dark.…”
Section: Introductionmentioning
confidence: 99%